STRATEGI KOMUNIKASI PEMASARAN DIGITAL DALAM MENINGKATKAN CITRA JANJI JIWA & TOAST DI SARANA SQUARE JILID 767 MELALUI APLIKASI JIWA+ - Alfiyyah Rafiqah; Murtiadi; Andi Banus Achir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has encouraged companies to implement more effective marketing communication strategies to strengthen their brand image. One of these strategies is implemented by Janji Jiwa & Toast through the Jiwa+ application, which functions as a digital marketing communication platform. This study aims to analy the digital marketing communication strategy in improving the brand image of Janji Jiwa & Toast at Sarana Square Jilid 767 through the Jiwa+ application. This research employed a descriptive qualitative approach with a constructivist paradigm. Informants were selected using a purposive sampling technique, involving one Janji Jiwa & Toast Supervisor (SPV) as the key informant and two customers as supporting informants. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. This study applies the Integrated Marketing Communication (IMC) theory, including advertising, sales promotion, public relations, direct marketing, and personal selling, as well as the brand image theory consisting of strength, favorability, and uniqueness. The findings indicate that the digital marketing communication strategy implemented through the Jiwa+ application contributes positively to strengthening the brand image of Janji Jiwa & Toast. Features such as exclusive promotions, membership and reward point programs, product information, digital ordering services, and responsive customer interactions provide positive experiences for customers. The implementation of integrated marketing communication through the Jiwa+ application is considered effective in enhancing brand strength, improving service excellence, and creating unique brand characteristics that distinguish Janji Jiwa & Toast from its competitors. Therefore, the Jiwa+ application functions not only as a transaction platform but also as an effective digital marketing communication medium that supports the enhancement of Janji Jiwa & Toast's brand image at Sarana Square.